Serous cystadenoma of the tunica testis: A case of malignancy mimicry - David Ali; Michael Diamond; Samantha Williams; Jay Patel; Michael Dardik; Ronald Frank (Urology Case Reports, 2022)
Cystadenoma of the tunica of the adult male testis has rarely been reported in the literature. We report a case of an adult serous cystadenoma along with the radiological and pathological findings. The patient was a 40-year-old male with a slowly growing mass on the left testis. An ultrasound scan of left testis showed features highly suspicious for malignancy. Lactate dehydrogenase (LDH) was mildly elevated. Alpha feta-protein (AFP) and beta-human chorionic gonadotropin (beta hCG) were negative. We performed left radical orchiectomy. The pathological findings showed serous cystadenoma of the tunica of the testis. The patient remains asymptomatic.